STUDENT SATISFCATION TOWARDS SERVICE QUALITY IN THE DEPARTMENT OF ECONOMIC UNIVERSITAS NEGERI MEDAN - Aprinawati, Aprinawati; Lastriani, Elvi; Siahaan, Sabda Dian Nurani; Saragih, Lenti Susanna (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2023)
Satisfaction with academic services is something that needs to be considered in order to achieve quality services that ensure student satisfaction as the main stakeholder in educational service organizationsThis study aims to see the level of student satisfaction with the service quality focusing on academic aspect. This research was conducted in the Department of Economics, Faculty of Economics, Universitas Negeri Medan. There are five indicators of academic service satisfaction in this study, they are Tangible Aspects, Assurance Aspects, Empathy Aspects, Responsive Aspects, and Reliability Aspects. This research method is quantitative with questionnaire data collection techniques to 689 respondents, they are students of the Economic Study Program, Business Education Study Program, Office Administration Education Study Program, and Economics Education Study Program. The results showed that student satisfaction at the Faculty of Economics both in terms of Tangible, Assurance, Empathy, Responsiveness, and Reliability, overall dominant were in the Good and Excellent categories, but with some suggestions for improving service quality within in the Department of Economics in the future